The challenges of doing gender research in developing countries: Focus on Malawi (Journal of Comparative Social Work, 2009)
We aim to illustrate how the tenor and character of the initial importation of the concept of gender into the Malawian context continues to impact, construct, and pose challenges to the study of gender in Malawi. Ultimately, we argue that complex and ethnographically grounded approaches to studying gender in Malawi may serve as a corrective to a long legacy of conceptual imperialism that has ramifications for both the researched and researchers in Malawi.